محددات التنمية البشرية في الجزائر للفترة 1990-2019 - كركب, عيسى; بن الحبيب, طه (جامعة الوادي - University of Eloued, 2022)
This study aims to try to measure human development during the period 1990-2019, and in order to thus the descriptive approach was followed to present and clarify the theoretical concepts of human development, and the standard approach for modeling determinants of human development represented in per capita GDP and average life expectancy at birth, and the school enrollment rate for primary education to find out which of these variables affect the human development by applying the ARDL technique using annual data. The results of study concluded that there is a long-term equilibrium relationship between the human development and its determinants.
determinants of human development in Algeria for the period 1990-2019
مقال
Keywords: تنمية بشرية ; نموذجARDL ; تكامل مشترك ; الجزائر